2020
DOI: 10.1101/2020.05.25.114363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization ofmWakeexpression in the murine brain

Abstract: Structure-function analyses of the mammalian brain have historically relied on anatomicallybased approaches. In these investigations, physical, chemical, or electrolytic lesions of anatomical structures are applied, and the resulting behavioral or physiological responses assayed. An alternative approach is to focus on the expression pattern of a molecule whose function has been characterized and then use genetic intersectional methods to optogenetically or chemogenetically manipulate distinct circuits. We prev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 105 publications
1
1
0
Order By: Relevance
“…Liu et al (9) found that the circadian output molecule wide awake (WAKE) responds to CLK oscillations, reducing excitability in wake-promoting l-LN V s. This pathway upregulates the GABA A receptor resistant to dieldrin (RDL). They also found that the mammalian homolog of WAKE ( 9), mWAKE, is expressed in both the SCN and dorsal medial hypothalamus (99). These data support the notion that mWAKE is conserved in driving wakefulness by modulating firing rates.…”
Section: The Neural Network That Regulates the Circadian Clocksupporting
confidence: 52%
“…Liu et al (9) found that the circadian output molecule wide awake (WAKE) responds to CLK oscillations, reducing excitability in wake-promoting l-LN V s. This pathway upregulates the GABA A receptor resistant to dieldrin (RDL). They also found that the mammalian homolog of WAKE ( 9), mWAKE, is expressed in both the SCN and dorsal medial hypothalamus (99). These data support the notion that mWAKE is conserved in driving wakefulness by modulating firing rates.…”
Section: The Neural Network That Regulates the Circadian Clocksupporting
confidence: 52%
“…Brain cell dissociation was performed as described previously (Bell et al 2021;Kim et al 2021) using one female mouse per genotype. Mouse brain matrix (0.5 mm) was used to slice brains into coronal sections, and relative brain regions (cerebral cortex, striatum, midbrain) were dissected into Hibernate-A media with a 2% B-27 and GlutaMAX supplement (0.5 mM final).…”
Section: Cell Dissociation and Scrna-seqmentioning
confidence: 99%